First Spatial Distribution Analysis of Male Sea Turtles in the Southern Gulf of Mexico - Cuevas, Eduardo; Putman, Nathan F.; Uribe-Martínez, Abigail; López-Castro, Melania C.; Guzmán-Hernández, Vicente; Gallegos-Fernández, Sandra A.; Liceaga-Correa, María de los Ángeles; Trujillo-Córdova, Jorge A.; González-Díaz-Mirón, Raúl de Jesús; Negrete-Phillipe, Ana; Acosta-Sánchez, Héctor H.; Martínez-Portugal, Rosa C.; et al. (Frontiers in Marine Science, 2020)
In the Gulf of Mexico, the bulk of published studies for sea turtles have focused on northern (United States) waters where economic resources are centered, with fewer studies in the southern portion of the basin, resulting in significant knowledge gaps in these underrepresented areas. Similarly, publications on adult sea turtles are dominated by research on females that come ashore to nest and can be readily studied (e.g., through the collection of biological samples and the application of satellite-telemetry devices), whereas information on adult male sea turtles is scarce. The goal of this paper is to begin filling these knowledge gaps by synthesizing available data on adult male sea turtles in the southern Gulf of Mexico. We used satellite-telemetry, boat- and drone-based surveys, and stranding records combined with ocean circulation modeling to better understand the spatial distribution of male loggerhead (Caretta caretta), green (Chelonia mydas), hawksbill (Eretmochelys imbricata), and Kemp’s ridley (Lepidochelys kempii) sea turtles in the southern Gulf of Mexico. These spatially explicit analyses will provide context for opportunistically collected data on male sea turtles and better contribute to the management and restoration of sea turtle populations that use the Gulf of Mexico. Moreover, this synthesis can serve as a launching point for directed studies on male sea turtles in this region.